Green Purchase Intention During Covid-19 Pandemic Toward Natural Skincare Product (The Indonesian Journal of Business Administration, 2021)
Indonesia also named as the Asia's quickest-growing beauty market for beauty in terms of compound annual growth rate with woman population 135 million. Skin care products had the largest value share of 31.1% in 2018 and forecast to record the fastest growth and maximum share with a value CAGR of 9.6% over 2018-2023. Starting to embrace the natural beauty care products regarding their wellness and health. Natural ingredients in skin care products work efficiently with the body system, repair, rejuvenate and enhance it. In the early of 2020, The World Health Organization (WHO) declared the outbreak of infectious disease COVID-19 (Corona Virus Disease-2019) as a pandemic on 11 March 2020. COVID-19 caused by SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2). This COVID-19 pandemic changes the way consumers purchase and consume product, including the beauty and skincare industry. This study uses a deductive research approach, and quantitative research method by distributing questionnaire to gain the data from skincare female users who domicile in Jakarta and Bandung, with 186 respondents. The result show that in the situation of COVID-19, the respondent attitude is influenced by health and environment consciousness. Furthermore, appearance consciousness has a weak influence and not significantly influenced their attitude. Aside from that, social influence doesn't influence their attitude at all regarding buying the natural skincare. As a final result the attitude has strong positive and significant influence toward green purchase intention regarding buying natural skincare. The final result of this study is a marketing strategy that uses the 4P's marketing mix. The product based on the potential beauty trend in 2021 and diversification assisted by collaborations with beauty influencers. The price should be affordable and colored with seasonal discounts, promos, and free delivery. The best options place to sell the product is to utilize the e-commerce, wholesaler, and social media to gain the mass. Furthermore, the promotion, it is better maximized at social media, collaborate with beauty influencers, endorsement, sponsorship for beauty events, and assign beauty ambassadors. Keywords: Attitude, Beauty Trend, COVID-19, Green Purchase Intention, Natural, Skincare